Applying haldi to the bride and groom - Mumbai Archive Project Team (Jio Institute, 2024)
During the haldi (turmeric) ceremony, a paste made from turmeric, sandalwood, and other ingredients is applied to the bride and groom. This application is done either by hand or using mango leaves, starting typically from the feet and moving upwards to the arms and face.